Marketing Strategies Used by Tobacco Companies Targeting the Queer Community - Kendra Lewis; Diamond Cunningham; Pamela Valera (SAGE Publishing, 2024)
Background: This study described the marketing strategies tobacco companies use to advertise tobacco products to the Queer community. Methods: In this secondary qualitative analysis, 15 Queer participants were interviewed to explore their life experiences with tobacco product advertisements during the early days of the COVID-19 pandemic. Results: Participants self-reported as male (n = 5), followed by female (n = 4), gender non-binary (n = 4) and, transgender (n = 2). In addition, most participants identified as Black/African American (n = 7) or White (n = 7). Many participants identified as Bisexual (n = 5) or Queer (n = 4). Using narrative analysis, the themes for this study were: (1) tobacco and vaping companies target minoritized and Queer people; (2) tobacco and vape companies maintain their presence by sponsoring local Lesbian, gay, bisexual, transgender, questioning, intersex, asexual, and other community (LGBTQIA+) bars and Pride events, often through giveaways and coupons; and (3) the use of social media influencers represents a new social marketing technique. As a result, Queer participants were more likely to encounter many different types of advertisements from tobacco companies and, most recently, social media influencers. Conclusion: Social media influencers are a new factor that needs further study to understand the new tobacco advertising landscape.